1961
DOI: 10.1084/jem.114.6.961
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Acute Phase Protein

Abstract: PLATES 90 TO 92

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
1

Year Published

1977
1977
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(53 citation statements)
references
References 18 publications
5
47
0
1
Order By: Relevance
“…The demonstration that colchicine-treated animals showed many more and stronger staining positive cells than did untreated animals may partially explain previous difficulties encountered in demonstrating CRP-producing cells in liver employing immunofluorescent methods (18). In those studies, in which colchicine was not administered, the rapid secretion rate in most cells would have greatly diminished the likelihood of detecting positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that colchicine-treated animals showed many more and stronger staining positive cells than did untreated animals may partially explain previous difficulties encountered in demonstrating CRP-producing cells in liver employing immunofluorescent methods (18). In those studies, in which colchicine was not administered, the rapid secretion rate in most cells would have greatly diminished the likelihood of detecting positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we propose that the generation of oxidized PtC on the cell surface, and͞or an alteration in the lipid milieu of the membrane in which PtC are found (as noted below) lead to exposure of PC moieties, which could mediate CRP binding. CRP has been reported to bind to cell membranes, as well as to intracellular components such as chromatin-containing H1 and small nuclear ribonucleoprotein (30)(31)(32). Initial evidence for the binding specificity of CRP to cells was provided by immunohistochemical studies demonstrating that CRP was associated with cell membranes of damaged and necrotic cells, but not normal cells, at sites of inflammation and tissue necrosis (30).…”
Section: Crp Frequently Colocalizes With the Eo6 Epitope In Human Athmentioning
confidence: 99%
“…CRP has been reported to bind to cell membranes, as well as to intracellular components such as chromatin-containing H1 and small nuclear ribonucleoprotein (30)(31)(32). Initial evidence for the binding specificity of CRP to cells was provided by immunohistochemical studies demonstrating that CRP was associated with cell membranes of damaged and necrotic cells, but not normal cells, at sites of inflammation and tissue necrosis (30). Recently, Gershov et al (2) reported that CRP binds to the surface membrane of apoptotic cells and subsequently promotes clearance, but the ligand mediating such binding was not characterized.…”
Section: Crp Frequently Colocalizes With the Eo6 Epitope In Human Athmentioning
confidence: 99%
“…gets deposited at sites of tissue damage and inflammation (12,13). Two types of molecular contacts are known for the binding of CRP to its ligands, one that requires calcium ions (Ca 2ϩ ) and another that does not require Ca 2ϩ and instead is inhibited by Ca 2ϩ (2).…”
mentioning
confidence: 99%